EDUCAÇÃO FINANCEIRA NO ENSINO MÉDIO: CONTRIBUIÇÕES DE UMA EXPERIÊNCIA FORMATIVA - Frozza, Mateus Sangoi (2023)
Preparing students to understand the increasingly complex situations involving financial issues and their numerous and varied products is the main objective of Financial Education. Financial Education is present in various means of information in modern society, being indispensable in the scientific field and in the education of citizens. Currently, in Brazil, there is a growing movement and initiatives for the insertion of Financial Education in education, in its most varied levels of education. The research we develop is positioned in the area of teaching Financial Education and financial literacy. The work, developed in the context of qualitative and quantitative research, aimed to investigate what and how to teach the discipline of Financial Education for High School. To this end, a literature review was carried out that encompasses the theoretical foundations and research elements, Financial Education, financial literacy and financial mathematics. We observed a sample of 73 students, 31 enrolled in the first year of high school and 42 in the second year of Colégio Antônio Alves Ramos (Pallotti). We base our exploration on data constructed by two questionnaires that were applied in the Financial Education discipline. The questionnaires were organized, for the most part, with questions based on problem situations and adapted from the National Institute of Educational Studies and Research Anísio Teixeira (INEP), from the questionnaire applied for the enrollment process in the National High School Examination (ENEM) and of studies by authors who are references, such as the financial literacy questionnaire of the Organization for Economic Co-operation and Development (OECD). For the treatment, analysis and interpretation of data, statistical computational tools were used in the theoretical framework of statistical analysis, with the support of the CHIC software. The data obtained in the research allowed the elaboration of a program for the discipline of Financial Education. That is, to present a teaching proposal for the strengthening of Financial Education and its consolidation in the high school curriculum, in view of the legal obligation and social need for its teaching in Brazilian schools. The results obtained show that students who take the subject of Financial Education in High School tend to have a greater understanding of everyday aspects of economic life, as well as greater awareness of planning and exercising financial citizenship. The school and society, as a whole, need to reflect and advance towards the development of Financial Education practices, as students, especially those participating in this research, will be future workers and, consequently, will have important repercussions on the country's economy.